In an attempt to add ligands to the sixth (axial) position of vanadyl bis-acetylacetonate: A unique tetranuclear vanadyl species - Lalancette, Roger; Bernal, Ivan (European Journal of Chemistry, 2023)
We have explored the interaction of [(acac)2V=O] (acac = acetylacetone) with a series of potential ligands which were chosen because of their expected ability to attach themselves onto its sixth (axial) position. Furthermore, some of the species chosen were expected to have the capability of linking pairs of [(acac)2V=O] molecules, thus creating magnetically coupled substances whose behavior would be interesting to document by magnetic as well as structural methods. Some of the synthetic results were surprising in that unexpected products were obtained which we had not envisioned; specifically, herein we describe a tetranuclear vanadyl cluster (Crystal data for C38H51N4O17ClV4: orthorhombic, space group Pca21 (no. 29), a = 26.4698(3) Å, b = 13.5167(2) Å, c = 12.7659(2) Å, V = 4567.44(11) Å3, Z = 4, μ(CuKα) = 7.842 mm-1, Dcalc = 1.53 g/cm3, 41277 reflections measured (6.538° ≤ 2Θ ≤ 137.892°), 7841 unique (Rint = 0.0428, Rsigma = 0.0421) which were used in all calculations; the final R1 was 0.0675 (I > 2σ(I)) and wR2 was 0.1641 (all data)), which is unusual in several aspects of its composition as well as its stereochemistry.